PENGARUH PENGGUNAAN E-BOOK TERHADAP HASIL BELAJAR BAHASA INDONESIA PADA KELAS VII DI SMP NEGERI 13 MAKASSAR - R, M. Irwansyah; H, Nurhikmah; Valentino Sinaga, Andromeda (Indonesian Journal of Educational Technology, 2024)
This study aims to determine the effect of e-book use on student learning outcomes in Indonesian language subjects for class VII at SMP Negeri 13 Makassar. The use of E-books in the learning process is considered capable of improving student learning outcomes by attracting students' attention to read the material in the E-book. The approach used in this study is a quantitative approach. This study uses an experimental research type, where this type of research is used to compare the learning outcomes obtained before the implementation of E-book-based learning media and after the implementation of E-book-based learning media on Indonesian language learning outcomes in class VII at SMP Negeri 13 Makassar. This study uses an experimental research type, so in collecting data can be done by means of questionnaires, tests, and observations or observations. The population of this study was all class VII students at SMP Negeri 13 Makassar. The samples taken were class VII F students totaling 28 students and class VII J students totaling 29 students. This research was conducted at SMP Negeri 13 Makassar from July 11 to July 26, 2023. This school is located at Jalan Tamalate VI No.2, Kassi-Kassi, Rappocini District, Makassar City, South Sulawesi. In this school, class VII is divided into 11 classes where class VII F consists of 28 students and class VII J consists of 29 students